2008
DOI: 10.1111/j.1476-4431.2008.00286.x
|View full text |Cite
|
Sign up to set email alerts
|

Lactate: physiology and clinical utility

Abstract: Objective: To review the physiology of lactate production and metabolism, the causes of lactic acidosis, and the current applications of lactate monitoring in humans and animals. Data sources: Human and veterinary studies. Summary: Lactate production is the result of anaerobic metabolism. Tissue hypoxia due to hypoperfusion is the most common cause of lactic acidosis. Studies in critically ill humans have shown that serial lactate monitoring can be used to assess the severity of illness and response to ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
121
1
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(137 citation statements)
references
References 67 publications
5
121
1
10
Order By: Relevance
“…1) situaram-se discretamente acima das concentrações normais para a espécie, utilizandose medidores portáteis, cuja variação, segundo Stevenson et al (2007) e Allen et al (2008), é de 1,2-3,1mmol/L, e dentro das concentrações descritas por Hughes (1999;, para o método enzimático, de 0,3-2,5mmol/L. A glicemia das cadelas também estava dentro dos padrões de referência propostos para a espécie por Kaneko (1997) Souza et al (2006), no sangue venoso, cujos valores ao nascimento foram, respectivamente, de 6,262,7mmol/L e de 5,562,31mmol/L.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…1) situaram-se discretamente acima das concentrações normais para a espécie, utilizandose medidores portáteis, cuja variação, segundo Stevenson et al (2007) e Allen et al (2008), é de 1,2-3,1mmol/L, e dentro das concentrações descritas por Hughes (1999;, para o método enzimático, de 0,3-2,5mmol/L. A glicemia das cadelas também estava dentro dos padrões de referência propostos para a espécie por Kaneko (1997) Souza et al (2006), no sangue venoso, cujos valores ao nascimento foram, respectivamente, de 6,262,7mmol/L e de 5,562,31mmol/L.…”
Section: Resultsunclassified
“…Seu uso em pequenos animais vem sendo preconizado, e vários estudos foram feitos demonstrando seu papel na medicina intensiva (Pang e Boysen, 2007;Allen et al, 2008). Os valores de lactato descritos em cães adultos foram de 1,57±0,47mmol/L (Hughes et al,1999) ou de 1,1 a 2,5mmol/L (Lagutchik et al, 1998).…”
unclassified
“…They concluded that lactate could be a suitable biochemical parameter for predicting intestinal obstruction or in the follow-up of intestinal obstruction. In present study, dehydration and intestinal ischemia could be the causes for hypoperfusion and increased lactate level (Allen & Holm 2008). …”
Section: Biochemical Findingsmentioning
confidence: 99%
“…O lactato sérico pode proporcionar a avaliação do grau de oxigenação dos tecidos, uma vez que a produção de lactato é inversamente proporcional à oxigenação tecidual, sendo o resultado do catabolismo anaeróbico da glicose CROWE;ALLEN;HOLM, 2008). Ou seja, a oxigenação reduzida pelos baixos níveis de hemoglobina resulta em hipóxia, a qual aciona o metabolismo anaeróbico, caracterizando uma correlação inversa entre os níveis de lactato e hemoglobina (CICHOTA, 2007).…”
Section: O Uso De Exames Complementares No Gatilho Transfusionalunclassified